Palladium catalyzed domino C-H activation strategy: An access to 9- fluorenones. Issue 2 (11th January 2019) - Patel, Anuj; Shaikh, Mahommedumar; Chikhalia, Kishor
Abstract: Palladium catalyzed domino C-H functionalization reaction of arylaldehyde with dihaloarene has been developed to access 9-flourenone molecules. Bidentate ligand assisted strategy, single step reaction, high yield and excellent functional group tolerance make this method concise and effective for the synthesis of 9-flourenone. In addition, proposed method has been successfully employed to synthesise Tilorone in gram scale. Graphical abstract: